2010
DOI: 10.1182/blood-2010-06-291922
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of tyrosine kinase inhibitors (TKIs) as third-line therapy in patients with chronic myeloid leukemia in chronic phase who have failed 2 prior lines of TKI therapy

Abstract: We analyzed a cohort of 26 patients with chronic myeloid leukemia who had failed imatinib and a second tyrosine kinase inhibitor but were still in first chronic phase and identified prognostic factors for response and outcomes. The achievement of a prior cytogenetic response on imatinib or on second-line therapy were the only independent predictors for the achievement of complete cytogenetic responses on third-line therapy. Younger age and the achievement of a cytogenetic response on second line were the only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
63
1
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 12 publications
8
63
1
4
Order By: Relevance
“…In fact, further assessments did not contribute to a better definition of poor-risk patients. We reported previously that poor responders to second-line 2G-TKIs obtain very limited benefit from a third-line TKI, 28 and indeed, patients who had a BCR-ABL1/ ABL1 ratio Ͼ 10% at 3 months after starting first-choice 2G-TKI had a very low 4-year c-CCyRS of 11.2% compared with 67.2% for the rest of the population (P ϭ .0001, Figure 1D). Clearly, a high 3-month transcript level identifies patients with intrinsic resistance to TKI therapy, which appears not to be improved by changing to an alternative TKI.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…In fact, further assessments did not contribute to a better definition of poor-risk patients. We reported previously that poor responders to second-line 2G-TKIs obtain very limited benefit from a third-line TKI, 28 and indeed, patients who had a BCR-ABL1/ ABL1 ratio Ͼ 10% at 3 months after starting first-choice 2G-TKI had a very low 4-year c-CCyRS of 11.2% compared with 67.2% for the rest of the population (P ϭ .0001, Figure 1D). Clearly, a high 3-month transcript level identifies patients with intrinsic resistance to TKI therapy, which appears not to be improved by changing to an alternative TKI.…”
Section: Discussionmentioning
confidence: 54%
“…Interestingly, both curves reach a plateau after the initial 12 months despite the fact that patients continue to have "events," which indicates that patients who have to discontinue their second-line therapy because of side effects fared very well on third line therapy, as reported previously. 28 Primary cytogenetic resistance to imatinib and a high Sokal risk score were the only pre-second-line therapy independent predictors for OS. This is consistent with previous reports by us and others in which patients with upfront cytogenetic resistance are less likely to respond to second-line therapy.…”
Section: Discussionmentioning
confidence: 92%
“…These CP-CML response rates appeared to be higher than those reported in patients who had received second-generation TKIs (nilotinib, dasatinib, and bosutinib) after resistance and/or intolerance to 2 prior TKIs. [6][7][8] Parallel to the high response rates to ponatinib in patients with refractory CML or Ph 1 ALL, with continued follow-up of the study an accumulation of arterial occlusive events (AOEs) was observed. Elective dose reductions were recommended for patients remaining in the study.…”
Section: Introductionmentioning
confidence: 99%
“…3 Twenty-one patients in whom second-line dasatinib or nilotinib failed were treated with the alternative tyrosine kinase inhibitor as previously described. 10 Complete, partial and major cytogenetic responses were defined using standard criteria. …”
Section: Patients Treated With Tyroskine Kinase Inhibitorsmentioning
confidence: 99%